A new technical study on the characteristics of Nickel-Titanium Orthodontic archwires using stimulated infrared thermography - Chahine, Nafez (International Journal of Dental Materials, 2022)
Background: Clear aligner therapy (CAT) is a prominent orthodontic treatment option. CAT was formerly only used to treat mild malocclusions, but with developments in technology, it can now treat much more complex malocclusions. With the increasing popularity of CAT and technological improvements, led to the development of Invisalign’s SmartTrack technology, the first commercially available aligner material that used multi-layer plastic to facilitate tooth movement. Multiple layers provide superior mechanical properties that eluded previous single layer plastics.Aim: To study the cytotoxicity properties of different thermoplastic multilayer clear aligner materials on human primary gingival fibroblasts (HGFs).Materials and methods: Three multilayered clear aligner materials were considered in this study: SmartTrack (Align Technology, San Jose, CA, USA), Zendura FLX (Bay Materials, Fremont, CA, USA), and ComfortTrack (Great Lakes Dental Technologies, Tonawanda, NY, USA). The samples were incubated at 37oC in DMEM (0.1 mg/mL) for 21 days. The cell viability of HGFs cultured with each sample medium was then compared to a negative control assessed by MTT assay.Results: The results showed slight toxicity for each one of the samples tested. The highest cytotoxicity level seen in the HGFs was SmartTrack (65.5% ± 2.5 of cell viability), followed by Zendura FLX (72.3% ± 8.6), and the least was observed by ComfortTrack (80.8% ± 2.1).Conclusion: The Under the experimental conditions of the study, all of the materials tested displayed slight levels of cytotoxicity. SmartTrack was measured as the most cytotoxic. There were no statistical differences found between the three aligner materials (P< 0.05).